Efficacy of hepatitis B vaccination in children with rheumatic diseases. Issue 7 (24th June 2021) - Kohagura, Toaki; Kawabe, Shinji; Abe, Naoki; Nakaseko, Haruna; Iwata, Naomi
Abstract: Background: Vaccination to prevent hepatitis B (HB) virus infection is important for children undergoing immunosuppressive treatment. Information on the efficacy of HB vaccination in children with rheumatic diseases undergoing immunosuppressive therapy is scarce. Methods: Children with rheumatic diseases administered HB vaccine during immunosuppressive treatment between May 2013 and September 2016 were enrolled. Patients were vaccinated three times (primary series). Those who remained seronegative after the primary series received a secondary series of vaccinations. Patient baseline characteristics and treatment details from the medical records were retrospectively investigated. The proportion of patients that was seropositive for HB virus antibody after primary‐and secondary series of vaccinations was calculated. Associations between immunosuppressants and serostatus were evaluated. Results: Fifteen of 26 patients (58%) produced anti‐hepatitis B surface antibody (anti‐HBs) after the primary vaccinations. Eight of 10 patients (80%) taking methotrexate and 3 of 11 (27%) taking mycophenolate mofetil (MMF) were seropositive. Multivariate analysis adjusted for dosage of prednisolone per body weight. Multivariate analysis showed MMF was a factor impeding seroconversion (odds ratio 0.093, 95% confidence interval 0.014–0.615). In six of seven patients (86%) who received a secondary series of vaccinations, anti‐HBs were produced. Conclusions: MMF may impede seroconversion after a primary series of HB vaccinations, thus requiring secondary series of vaccinations in pediatric patients with a rheumatic disease undergoing immunosuppressive therapy.